POURQUOI CONTINUER A VOTER EN REPUBLIQUE DEMOCRATIQUE DU CONGO? - TONGOLO, Hervé NDUTE (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
Reading several authors, we wonder if we still need to vote. Not only in DR Congo but in several other countries, even in the West. According to a study, while voting remains a right and a duty, its interest is declining more and more. Why vote when campaign promises are just illusions? Why vote when non-elected bodies always confiscate the popular decision? Why vote when Goldmann Sachs is taking financial power in the world and in Africa in particular? Why vote when the results often don’t reflect the vote cast? Why vote when elected officials do not defend the interests of all? It seems that the outcome is being decided elsewhere rather than at the ballot box. The article explores the history of democracy and elections in DR Congo since independence. It summarizes controversial views on whether or not to continue voting. Like a failed state, election results often do not reflect the will expressed; and those proclaimed do not also accomplish for the general interest. All things considered, despite the rise in abstention and plummeting rates of participation in elections, as the result of the survey presents, our objective is to stimulate the Congolese population to vote again.